Effect of Qur’anic recitation on chondrocytes growth using scratch wound assay: work in progress - Hashim, Rosyafirah; Zainuddin, Zainul Ibrahim; Sha'ban, Munirah (2016)
Purpose: This study aims to identify the potential effects of the Qur’anic recitation,particularly Surah Al-Fatihah on the wound healing activity of chondrocytes derived from rabbit articular cartilage.